Assessment of causality of natriuretic peptides and atrial fibrillation and heart failure: a Mendelian randomization study in the FINRISK cohort. Issue 10 (23rd August 2020) - Geelhoed, Bastiaan; Börschel, Christin S; Niiranen, Teemu; Palosaari, Tarja; Havulinna, Aki S; Fouodo, Césaire J K; Scheinhardt, Markus O; Blankenberg, Stefan; Jousilahti, Pekka; Kuulasmaa, Kari; Zeller, Tanja; Salomaa, Veikko; et al.
Abstract: Aims: Natriuretic peptides are extensively studied biomarkers for atrial fibrillation (AF) and heart failure (HF). Their role in the pathogenesis of both diseases is not entirely understood and previous studies several single-nucleotide polymorphisms (SNPs) at the NPPA-NPPB locus associated with natriuretic peptides have been identified. We investigated the causal relationship between natriuretic peptides and AF as well as HF using a Mendelian randomization approach. Methods and results: N-terminal pro B-type natriuretic peptide (NT-proBNP) ( N  = 6669), B-type natriuretic peptide (BNP) ( N  = 6674), and mid-regional pro atrial natriuretic peptide (MR-proANP) ( N  = 6813) were measured in the FINRISK 1997 cohort. N  = 30 common SNPs related to NT-proBNP, BNP, and MR-proANP were selected from studies. We performed six Mendelian randomizations for all three natriuretic peptide biomarkers and for both outcomes, AF and HF, separately. Polygenic risk scores (PRSs) based on multiple SNPs were used as genetic instrumental variable in Mendelian randomizations. Polygenic risk scores were significantly associated with the three natriuretic peptides. Polygenic risk scores were not significantly associated with incident AF nor HF. Most cardiovascular risk factors showed significant confounding percentages, but no association with PRS. A causal relation except for small causal betas is unlikely. Conclusion: In our Mendelian randomization approach, we confirmed an association between common genetic variation at the NPPA-NPPB locus and natriuretic peptides. A strong causal relationship between natriuretic peptides and incidence of AF as well as HF at the community-level was ruled out. Therapeutic approaches targeting natriuretic peptides will therefore very likely work through indirect mechanisms.